COMPUTATIONAL INVESTIGATION OF SPECTROSCOPIC PARAMETERS IN PUTATIVE SECONDARY STRUCTURE ELEMENTS FOR POLYLACTIC ACID AND COMPARISON WITH EXPERIMENT - IRSAI, Izabella; LUPAN, Alexandru; MAJDIK, Cornelia; SILAGHI-DUMITRESCU, Radu (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Putative elements of secondary, tertiary and quaternary structure were examined for polylactic acid chains, attempting a parallel with secondary structure elements known from protein biology and also attempting an estimate, based on accurate atomic-level calculations, of interaction energies between polylactic acid chains. Spectroscopic parameters were predicted for all types of structure examined, in an attempt to aid our on-going efforts in synthesis and characterization of polylactic acid variants.